Impact pathways of voluntary sustainability standards on smallholder coffee producers in Honduras: Price premiums, farm productivity, production costs, access to credit. (September 2022) - Estrella, Andrea; Navichoc, David; Kilian, Bernard; Dietz, Thomas
Highlights: Certifications are limited in improving the economic conditions of smallholder coffee producers in Honduras. Certified producers receive a higher price for the coffee they sell. However, certification does not improve overall household incomes. Certified producers have a probability between 56% and 58% of living under the national poverty line. Abstract: Coffee production in Honduras is under constant economic pressure, social unrest, and climate challenges. This largely affects the living conditions of thousands of smallholder coffee producers as the weakest actors in the coffee value chain and exacerbates the level of poverty and inequality that they face. A considerable part of the coffee production in Honduras is under different Voluntary Sustainability Standards (VSS); a major goal of these standards is to improve the livelihoods of smallholder farmers. Thus, this paper assesses the economic impact of Fairtrade, UTZ, and 4C on smallholder producers against a control group, using Propensity Score Matching with data of the coffee year 2015/2016. The main economic variables studied in this paper are gross profit, household income, and poverty likelihood. In addition, this study develops a conceptual framework to explore different impact pathways –price premium, farm productivity, production costs, and access to credit– that could improve farm performance and ultimately the economic conditions of farmers. The results of this study suggest that smallholder coffee producers in Honduras are not obtaining a higher economic impact from the different certifications assessed. Among the pathways, only the price premium was statistically significant for the three certifications assessed, displaying higher prices per unit than the control group. In line with their economic conditions, these producers have a probability between 56% and 58% of living under the national poverty line according to the Poverty Probability Index (PPI), concluding that certifications do not always improve the livelihood of coffee producers.